2000
DOI: 10.1042/bj3510319
|View full text |Cite
|
Sign up to set email alerts
|

Anti-(herpes simplex virus) activity of 4′-thio-2′-deoxyuridines: a biochemical investigation for viral and cellular target enzymes

Abstract: The antiviral activity of several nucleoside analogues is often limited by their rapid degradation by pyrimidine nucleoside phosphorylases. In an attempt to avoid this degradation, several modified nucleosides have been synthesized. A series of 4h-thio2h-deoxyuridines exhibits an anti-[herpes simplex virus (HSV)] activity significantly higher (20-600 times) than that shown by the corresponding 4h-oxy counterpart. We investigated the mode of action of these compounds and we found that : (i) several 4h-thio-2h-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Although most T-dCyd was converted to T-dUrd, there was little evidence that T-dUrd was phosphorylated by dThd kinase and then converted to T-TMP via thymidylate synthase: 12% of dCyd was converted to dThd nucleotides in HCT116 cells, however, only 0.2% of T-dCyd was converted to T-dThd nucleotides. This observation supports previous studies (Secrist et al, 1991;Verri et al, 2000) that indicated T-dUrd was a poor substrate for dThd kinase. In addition, T-dUrd was not a substrate for dThd phosphorylase in crude cell extracts of .…”
Section: Metabolism and Depletion Of Dnmt1 By T-dcydsupporting
confidence: 92%
“…Although most T-dCyd was converted to T-dUrd, there was little evidence that T-dUrd was phosphorylated by dThd kinase and then converted to T-TMP via thymidylate synthase: 12% of dCyd was converted to dThd nucleotides in HCT116 cells, however, only 0.2% of T-dCyd was converted to T-dThd nucleotides. This observation supports previous studies (Secrist et al, 1991;Verri et al, 2000) that indicated T-dUrd was a poor substrate for dThd kinase. In addition, T-dUrd was not a substrate for dThd phosphorylase in crude cell extracts of .…”
Section: Metabolism and Depletion Of Dnmt1 By T-dcydsupporting
confidence: 92%
“…Although they all likely act on the viral DNA Pol, further investigation will be required to substantiate this. Such would be the case, for example, for derivatives of acyclic/carbocyclic guanosine analogs [219], 4'-thio-2'-deoxyuridines [220]. (1S',2R')-9-[[1',2'-bis(hydroxymethyl)cycloprop-1-yl]methyl]guanine (A-5021) [221], cyclohexenylguanine [222], 5-alkyl-2-thiopyrimidine nucleosides [223], conformationally locked (north)-methanocarbathymine nucleosides [224], acyclic C-nucleoside analogs of 2,6-dichloro-and 2,6,7-trichloroimidazo [225] pyridine [226], methylenecyclopropane analogs of nucleosides [227], 3 -formyl -2, 5, 6 -trichloro -1 -( beta -D -ribofuranosyl) indole (FTCRI) and its 3-cyano homologue (CTCRI) at the 3-position, chlorinated nucleosides pyrazolo [228] indole nucleoside analogs.…”
Section: Perspectives For Drug Designmentioning
confidence: 99%
“…The synthesis of 2'-deoxy-4'-thiouridines, which exhibit an anti-HSV activity significantly higher (20-600 times) than that shown by the corresponding 4'-oxo counterpart, is one of attempts to avoid this degradation. Verri et al [35] have synthesized 5-substituted 2'-deoxy-4'-thiouridines ( Fig. 3-1) according to the procedure previously described by Rahim et al [25] and investigated their mode of actions.…”
Section: ' or 3'-deoxy-4'-thionucleosidesmentioning
confidence: 99%